2017
DOI: 10.1007/978-3-319-68557-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones and/or Smartphones and Their Use in the Management of Dementia – Findings from the Research Studies

Abstract: At present, there is a significant increase in the number of older population groups worldwide. This accelerating trend in the rise of older population groups inevitably results in serious economic and social changes accompanied with a number of aging diseases such as dementia. The purpose of this review study is to explore the use of mobile phones and/ or smartphones and their benefits and limitations for patients with dementia. The methods include a literature review of available studies on this topic found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Case studies have shown that training people with dementia in the use of smartphones and tablet computers can be beneficial in maintaining activities of daily living (ADL; Bier et al, 2015 , 2018 ; Imbeault et al, 2018 ). However, a 2017 review found that few studies have investigated the use of smartphones by people with dementia ( Klimova, 2017 ). Furthermore, the studies included in this review discussed the use of specific apps and tracking systems developed by research teams as opposed to the day-to-day use of smartphones by people living with dementia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies have shown that training people with dementia in the use of smartphones and tablet computers can be beneficial in maintaining activities of daily living (ADL; Bier et al, 2015 , 2018 ; Imbeault et al, 2018 ). However, a 2017 review found that few studies have investigated the use of smartphones by people with dementia ( Klimova, 2017 ). Furthermore, the studies included in this review discussed the use of specific apps and tracking systems developed by research teams as opposed to the day-to-day use of smartphones by people living with dementia.…”
mentioning
confidence: 99%
“…It is thought that the use of mobile technologies to offer cognitive support could generalize to assist not only people living with dementia but also people experiencing similar cognitive limitations due to illnesses or disabilities such as stroke, mental illness, brain injury, and physical or sensory disability ( Koo & Vizer, 2019 ). Although predominantly focused on dementia and MCI, due to the paucity of literature on this topic reported in the studies of Kim and Lee (2017) and Klimova (2017) , the parameters of this review were expanded to include the use of smartphones and tablet devices by not only people with dementia and MCI but also older adults with cognitive impairment due to ABI. This review is interested in acquired cognitive impairment as opposed to the chronic cognitive impairment that may be experienced by people living with mental illness, physical or sensory disabilities.…”
mentioning
confidence: 99%